2015
DOI: 10.1002/jor.22983
|View full text |Cite
|
Sign up to set email alerts
|

Expression of growth differentiation factor 6 in the human developing fetal spine retreats from vertebral ossifying regions and is restricted to cartilaginous tissues

Abstract: During embryogenesis vertebral segmentation is initiated by sclerotomal cell migration and condensation around the notochord, forming anlagen of vertebral bodies and intervertebral discs. The factors that govern the segmentation are not clear. Previous research demonstrated that mutations in growth differentiation factor 6 resulted in congenital vertebral fusion, suggesting this factor plays a role in development of vertebral column. In this study, we detected expression and localization of growth differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…During development, cellular secretion of GDFs forms directional morphogenetic gradients . Recently, the expression and localization of GDF6 in developing spinal column of human fetus have been examined . The strong expression of GDF6 is especially shown throughout cartilaginous region of vertebrae at early developing period (8‐13 weeks of gestation) and in the developing IVDs (between 8 and 19 weeks of gestation) and is diminished from ossification areas.…”
Section: Gdfs In Ivd Development Homeostasis and Potential For Regenmentioning
confidence: 99%
See 1 more Smart Citation
“…During development, cellular secretion of GDFs forms directional morphogenetic gradients . Recently, the expression and localization of GDF6 in developing spinal column of human fetus have been examined . The strong expression of GDF6 is especially shown throughout cartilaginous region of vertebrae at early developing period (8‐13 weeks of gestation) and in the developing IVDs (between 8 and 19 weeks of gestation) and is diminished from ossification areas.…”
Section: Gdfs In Ivd Development Homeostasis and Potential For Regenmentioning
confidence: 99%
“…These could include cellular and acellular therapies delivered with and without instructive biomaterials and in conjunction with bioactive molecules or growth factors (see for recent in‐depth review). One such family of factors, growth differentiation factors (GDFs), appear to be an exciting prospect due to their crucial role in chondrogenesis (including differentiation to NP cells, namely, discogenesis) and cartilaginous tissue homeostasis . As such, the focus of this review is directed on the continuing development of regenerative strategies for IVD repair employing GDF family members and the potential therapeutic role of GDF6.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic regeneration strategies aim to abrogate this proinflammatory, catabolic positive feedback loop through the implantation of healthy cells and/or signalling molecules to instruct correct ECM production, particularly in the NP. One growth factor recently proposed for NP regeneration is growth differentiation factor 6 (GDF6), a member of the bone morphogenetic protein (BMP) family that plays important developmental roles in the formation of cartilaginous tissues, including the IVD (Clendenning & Mortlock, 2012;Settle et al, 2003;Tassabehji et al, 2008;Wei et al, 2016). GDF6 expression has been linked to anti-ageing effects in multiple tissues (Hisamatsu, Ohno-Oishi, Nakamura, Mabuchi, & Naka-Kaneda, 2016) and, whereas studies conducted in our laboratory and others do not suggest GDF6 expression decreases with degeneration (Gulati, Chung, Wei, & Diwan, 2015; Le Maitre, Freemont, & Hoyland, 2009), preclinical studies have demonstrated that injection of GDF6 into experimentally induced rabbit and ovine annular puncture models attenuates pro-inflammatory molecular changes and prevents progression of IVD degeneration (Miyazaki et al, 2018;Shen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…34,35 Collagen X is also expressed at endochondral ossification, by hypertrophic chondrocytes. 36 Interestingly, we have found strong CDMP-2 expression in hypertrophic chondrocytes in foetal spinal tissue, 37 and its expression has been linked with the delineation of bone boundaries in developing organisms. 28,29 Further studies are needed to determine the specific signaling pathway of CDMP-2 in regulating expression of specific extracellular matrix molecules both during development and in adult tissue maintenance, but the tendency for CDMP-2 to promote chondrogenic tissue renewal is encouraging from the perspective of therapeutic use in disc regeneration.…”
Section: Discussionmentioning
confidence: 87%